Genitourinary Syndrome Of Menopause: Clinic And Management - Ayala-Peralta, Félix (2017)
The genitourinary syndrome of menopause clinically is evident 4 to 5 years after menopause, and objective changes arepresent in 25-50% of all postmenopausal women. The most frequent symptoms are vaginal dryness ( 75%), dyspareunia(38%), and vaginal itching, vaginal discharge and pain (15%); and the diagnosis is based on clinical criteria. The principlestherapeutic are based on the restoration of urogenital physiology and relief of symptoms; including non-hormonal / lubricanttherapeutic options, systemic hormonal therapy, local estrogen therapy and other alternatives. The genitourinary syndromeof menopause is one of the most important determinants of sexual function and urogenital health, with a significant impact onthe quality of life related to female health.